Fractional Order PID Controlled Interleaved Boost converter Fed Shunt Active Filter System - Purigilla Venkata Ramkumar; Munagala Surya Kalavathi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Interleaved Boost Converter (ILBC) is a better converter between Photo Voltaic(PV) source and shunt active power filter. This paper deals with comparison of time domain outputs of PI and Fractional Order PID(FOPID) controlled ILBC fed shunt active filter in a grid connected PV system. The aim of this work is to minimize current ripple using ILBC between PV system and filter to improve the dynamic performance of shunt active filter. Closed loop monitored PI and FOPID systems are modeled, and the corresponding results are presented. MATLAB results of load voltage, current, converter voltage and currents with FOPID exhibits enhanced dynamic response. The proposed FOPID controlled ILBC Fed Shunt Active Filter system (ILBCFSAF) has advantages like low settling time, less peak over shoot and reduced steady state error in load voltage. The simulation results of ILBCSAF are compared with the corresponding hardware results.